Kualitas Pelayanan Pengaruhnya Terhadap Kepuasan Pelanggan Transportasi Online di Kota Makassar - Mustari Mustari; Muh. Ihsan Said (Seminar Nasional LP2M UNM, 2019)
Abstract. This study aims to explain the effect of service quality on customer satisfaction on users of online transportation services. This research is a verification study with that population, all online transportation users in Makassar city and a sample of 100 online transportation users. Data collection techniques used were observation, questionnaires and documentation. The testing techniques carried out included a questionnaire test consisting of a validity and reliability test, a classic assumption test consisting of a multicollinearity test, a heteroscedasticity test, a normality test, a simple linear regression analysis, a hypothesis test consisting of a t test and a coefficient of determination. The results showed that the quality of service is categorized as "good" in terms of indicators of reliability (reliability), responsiveness (responsiveness), assurance (assurance and certainty), empathy (caring), and tangible (physical form). While customer satisfaction is classified in the category of "high" in terms of indicators of the suitability of expectations, interest in reusing and willingness to recommend. Hypothesis testing results indicate that there is a relatively high influence between service quality on customer satisfaction on users of online transportation services in the city of Makassar Keywords: Service Quality, Customer Satisfaction